STRATEGI NARASI REIZUKA ARI DAN DAMPAKNYA TERHADAP KONSUMSI REMAJA PEREMPUAN DI TIKTOK - Celvin Dwi Putra Mudianto; Hera Nur Aini; Zainal Abidin Achmad (LENTERA: JOURNAL OF GENDER AND CHILDREN STUDIES, 2025)
In the digital era, TikTok has become an influential social media platform that shapes people's consumption behavior. This study aims to analyze the role of Reizuka Ari as a content creator in creating digital consumption trends through narrative strategies and assertive communication. The researcher used a qualitative approach with a narrative content analysis method on several videos uploaded by Reizuka Ari that review food and beauty products. The analysis results show that Reizuka Ari consistently conveys product information clearly and relatably through a distinctive language style, strong expressions, and attractive visuals. He also utilizes the TikTok affiliate feature and builds active interactions with his followers. The combination of narrative elements, visuals, and an honest and persuasive communication approach successfully creates emotional engagement with the audience and encourages consumptive actions. This study concludes that content creators like Reizuka Ari are information providers and strategic agents who can influence digital consumption patterns through effectively curated content. Keywords: Content Creator, Tiktok, Consumption Trends, Narrative Strategy, Digital Communication.